INDIKASI TINDAK PIDANA KORPORASI DI WILAYAH HUKUM POLDA BALI (STUDI KASUS PENYIDIKAN PT. BALICON) - Agus Indra Nugraha, I Putu; Surya Dharmajaya, Ida Bagus; Walesa Putra, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013, 2013)
Indications of corporation criminal law region of the Bali Police. On August 172010 Bapepam center based in Jakarta to Bali Police reported that PT. BaliconsultantLife Insurance conduct insurance business without permission of the Minister ofFinance of the Republic of Indonesia since 2008. The purpose of this research is toinvestigate criminal offenses done by the corporation law of the territory of Bali Police,also to know how the Bali Police to determine the corporation as a criminal and who isaccountable in the case of a crime committed by a corporation. In this research, usingempirical legal research, as it approaches the problem from the legislation in force andthe reality that exists in the society. Bali Police identifies action or error done bydirector or head of PT. Balicon an act or fault PT. Balicon accordance with theIdentification Theory. Bali Police, in state of asking the responsibility from director, healso asked PT. Balicon as the corporation to responsible for. This is dealing with thegovernment law No. 2, 1992 and No. 40, 2007.
Keywords: Indication, Criminal, Corporation, PT. Balicon